Multilingualism: A Paradoxical Dimension of Mother Tongue Education in Nepal - Magar, Bishnu (New Journey, 2023)
This paper explores and analyses the policy and practice of mother tongue education implemented by the government of Nepal which has rather become inexpressibly dormant. The quiescent and fugitive mentality of implementing agency has created a chaotic situation in an academic achievement of the ethnic groups of students who use their dialect and find difficulties in classroom instruction at school. This paper exuberantly brings out the subtle circumstances of classroom pedagogy on mother tongue education heavily suffering from the lack of human resources since the implementation of mother tongue education in 2007 in Primary level. This paper has dealt with the analysis of policy and practice, field opinions of teachers and principals and the reflexive facet of the researcher. The findings recapitulate that implementation of mother tongue education has been augustly welcomed; however, short comings on availability of human capital and classroom pedagogy concurrently devastated the academic achievements of mother tongue user children due to the medium of classroom instructions in Nepali and poorly developing English instruction system in the classroom.